ANALYSIS OF THE RECEPTION OF PUBLIC VIEWS ON GAY COUPLES ON TIKTOK @CHIKO_INGHAM ACCOUNT - Fadhilah, Sevia Nur; Istiqomah, Istiqomah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze public reception and perceptions of gay couples on TikTok, particularly focusing on how users interpret and respond to inclusive content related to sexual identity expression and LGBT advocacy. Method: Using a qualitative descriptive content analysis approach, data were collected through online interviews with followers of the TikTok account @chiko_ingham, allowing for an in-depth understanding of audience interpretations and attitudes. Results: The findings reveal that while visibility and acceptance of gay couples on social media have increased, public reactions remain diverse, encompassing supportive, neutral, and rejecting responses. These reactions align with Stuart Hall’s reception theory, categorized into three positions: dominant hegemonic (fully supportive), negotiated (partially accepting within personal or cultural constraints), and oppositional (rejecting based on cultural or religious norms). Novelty: This research contributes to the growing body of literature on digital media and gender studies by offering a nuanced understanding of how TikTok functions as a site of meaning-making and social negotiation surrounding sexual identity in contemporary society.